2019
DOI: 10.1038/s12276-019-0277-4
|View full text |Cite
|
Sign up to set email alerts
|

A brain somatic RHEB doublet mutation causes focal cortical dysplasia type II

Abstract: Focal cortical dysplasia type II (FCDII) is a cerebral cortex malformation characterized by local cortical structure disorganization, neuronal dysmorphology, and refractory epilepsy. Brain somatic mutations in several genes involved in the PI3K/AKT/mTOR pathway are associated with FCDII, but they are only found in a proportion of patients with FCDII. The genetic causes underlying the development FCDII in other patients remain unclear. Here, we carried out whole exome sequencing and targeted sequencing in paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…In the context of epilepsy, spontaneous seizures were reported in all studies that evaluated this phenotype. Postnatal rapamycin treatment, starting before or after seizure onset, sufficiently suppresses seizures in multiple models (Lim et al, 2015(Lim et al, , 2017Hsieh et al, 2016;Zhao et al, 2019;Onori et al, 2020). Interestingly, these studies consistently reported that mTORC1induced seizures occur independently of neuronal placement, and preventing this alteration did not prevent seizures.…”
Section: Conserved Mtorc1-dependent Phenotypes Across Pi3k-mtor and Gator1 Gene Variantsmentioning
confidence: 96%
“…In the context of epilepsy, spontaneous seizures were reported in all studies that evaluated this phenotype. Postnatal rapamycin treatment, starting before or after seizure onset, sufficiently suppresses seizures in multiple models (Lim et al, 2015(Lim et al, , 2017Hsieh et al, 2016;Zhao et al, 2019;Onori et al, 2020). Interestingly, these studies consistently reported that mTORC1induced seizures occur independently of neuronal placement, and preventing this alteration did not prevent seizures.…”
Section: Conserved Mtorc1-dependent Phenotypes Across Pi3k-mtor and Gator1 Gene Variantsmentioning
confidence: 96%
“…Upregulation of autophagy has been found to reverse disease-like phenotypes in animal models of FCD, PD, AD, etc. ( Lee et al, 2013 ; Frake et al, 2015 ; Zhao S. et al, 2019 ). Herein, we also found that rapamycin treatment improved novel object recognition memory and rescued LTP deficits in Rab39b KO mice, suggesting that rapamycin may also alleviate symptoms in XLID patients caused by RAB39B mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, the role of signals that regulate hamartin and tuberin activity as well as the mTORC1 substrates responsible for specific developmental events are only now being determined. Perhaps most striking is the fact that somatic mutations that cause mTORC1 pathway activation have been identified as a cause of a plethora of neurological diseases (Lee et al, 2012 ; Poduri et al, 2012 ; Parker et al, 2013 ; Lal et al, 2014 ; Baek et al, 2015 ; Baulac et al, 2015 ; Crino, 2015 ; D’Gama et al, 2015 , 2017 ; Leventer et al, 2015 ; Lim et al, 2015 ; Baulac, 2016 ; Korenke et al, 2016 ; Møller et al, 2016 ; Hanai et al, 2017 ; Park et al, 2018 ; Iffland and Crino, 2019 ; Kim et al, 2019 ; Pelorosso et al, 2019 ; Salinas et al, 2019 ; Zhao et al, 2019 ; Garcia et al, 2020 ). Thus, what has been learned by studying the TSC pathway may now be applied to an expanding number of patients.…”
Section: The Molecular Genetics Of Tscmentioning
confidence: 99%